MATHEMATICAL MODELING METHODS FOR ESTIMATING THE INTERNAL LOAD OF RESERVOIRS WITH HEAVY METALS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Increased turbidity of water in water bodies negatively affects the functioning of aquatic ecosystems and can complicate a number of water use aspects. Heavy metals adsorbed on the surface of bottom soil particles and suspensions increase the total content of pollutants in the water masses during agitation of bottom sediments. The negative effect of heavy metals on aquatic organisms is compounded by the fact that heavy metals are resistant to degradation for many years, they accumulate rapidly in aquatic organisms and are very slowly eliminated from organisms. Currently, hydrodynamic calculations are used to estimate the spread of turbidity fields. Numerical experiments based on a hydrodynamic model make it possible to continuously assess the spread of turbidity fields and calculate the consequences of possible hydraulic engineering measures related to the initiation of increased turbidity in the water area.
Keywords: reservoir; heavy metals; mathematical modeling; turbidity; bottom sediments